Diffusion Tensor Imaging in Parkinson's Disease and Parkinsonian Syndrome: A Systematic Review - Zhang, Yu; Burock, Marc A. (Frontiers in Neurology, 2020)
Diffusion tensor imaging allows measuring fractional anisotropy and similar microstructural indices of the brain white matter. Lower than normal fractional anisotropy is associated with loss of microstructural integrity and neurodegeneration. Previous diffusion tensor imaging in Parkinson’s Disease have demonstrated a multifocal pattern of abnormal fractional anisotropy in brain white matter structures and tracts. However, diffusion tensor imaging is not considered a diagnostic marker for the earliest Parkinson’s disease since anisotropic alterations present a temporally divergent pattern during the earliest Parkinson’s course. This article reviews previous diffusion imaging studies in Parkinson’s disease, in comparison with recent analyses based on imaging datasets from the Parkinson’s progression markers initiative (PPMI) – a large multicenter cohort of Parkinson’s research, aims to explain a complex pattern of microstructural alterations detected with diffusion tensor imaging over the Parkinson’s disease course. This article also discusses the challenges and utility of diffusion tensor imaging in detecting microstructural changes associated with dopaminergic nuclei and dopaminergic pathways, the roles of diffusion tensor imaging as a longitudinal marker for tracking Parkinson’s progression and treatment effects, and differentiation among Parkinsonism.